HUMAN SECURITY AND CIVIL LIBERTIES IN PROTEST POLICING: A COMPARATIVE STUDY OF INDONESIA AND SOUTH KOREA - Muhammad Fajhriyadi Hastira; Fathan Rafiqi; Ali Maksum; Septi Khairullah (Indonesian Perspective, 2025)
This study aims to analyze how the policing of demonstrations in Indonesia and South Korea reflects the relationship between human security and civil liberties in the context of post-authoritarian democracy. Using a qualitative approach with a Most Similar Systems Design (MSSD), this study combines thematic analysis and narrative comparison of legal documents, human rights institution reports, and national and international media sources. The results show that although both countries have electoral democratic systems, fundamental differences arise in how the state interprets and implements public security. In Indonesia, the policing of demonstrations tends to perpetuate the authoritarian legacy through coercive legalism and digital surveillance, which suppresses public participation. In contrast, South Korea maintains a relative balance between control and the protection of citizens' rights. These findings expand our understanding of how technology, law, and political culture interact in shaping security practices in democratic countries. Theoretically, this research confirms the importance of the human security paradigm in evaluating democratic governance. Practically, the results encourage institutional reform and transparency in the use of surveillance technology, aligning with human rights principles.